A Team's Journey Toward More Equitable Philanthropic Research and Evaluation Practices - and Spring, Kimberly; Mata, Maria Fernanda; Poirier, Jeffrey; Holmes, Allison; François, Amir (The Foundation Review, 2023)
This article describes the journey of the Research and Evaluation team at the Annie E. Casey Foundation to develop an approach that would allow us to rethink and deepen how we, as funders of research and evaluation, center equity in our practice. In particular, we explain how, through this process, we began to focus on what it means to orient research and evaluation toward participant owners and came to examine the assumptions, expectations, habits, and values that we held. These experiences have presented us with opportunities to learn and be open to new ways of engaging in our work. We illustrate what this has looked like through vignettes involving five different Casey Foundation research and evaluation projects and conclude with some of the core lessons that we have learned: View tension as an opportunity for creativity; build in and protect space and time for reflection; and develop rapport and trust to strengthen practice.